2011
DOI: 10.1021/jf201658g
|View full text |Cite
|
Sign up to set email alerts
|

Potential Health Implication of in Vitro Human Low-Density Lipoprotein–Vitamin E Oxidation Modulation by Polyphenols Derived from Côte d’Ivoire’s Oil Palm Species

Abstract: Antioxidant activities of polyphenolic compounds extracted (PPEs) from ripe fruits of oil palms are investigated by studying their in vitro effects on human low-density lipoprotein (LDL) oxidation. Four oil palm species ( Elaeis guineensis ) are issued from the National Centre of Agronomic Research of Côte d'Ivoire, of which two are parental varieties (HP1 and HP2), while the other two are crossing varieties (HP3 and HP4). The main identified compounds were rutin (HP3 and HP4) and caffeic and chlorogenic (5-ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Our results are in good agreement with Monde et al [30], where chlorogenic acid was reported as the major compound in oil palm fruits. In addition caffeic acid, rutin and quercetin were also detected.…”
Section: Resultssupporting
confidence: 93%
“…Our results are in good agreement with Monde et al [30], where chlorogenic acid was reported as the major compound in oil palm fruits. In addition caffeic acid, rutin and quercetin were also detected.…”
Section: Resultssupporting
confidence: 93%
“…Total McPC concentration was estimated by Folin–Ciocalteu's assay, with absorbance monitored at 760 nm (Mondé and others ). The spectrophotometric measurement was repeated 3 times for each extract and the average data was interpolated in a gallic acid calibration curve and expressed on a dry weight basis as mg of gallic acid equivalents per g of dry weight sample (mg GAE g −1 DW).…”
Section: Methodsmentioning
confidence: 99%
“…LDL was isolated from fresh plasma of healthy human subjects, obtained from the “French Blood Establishment,” in accordance with its ethical rules, and oxidizability was monitored at 234 nm for 5 μmol L −1 Cu 2+ oxidation as previously indicated (Mondé and others ). Briefly, isolated LDL was diluted to 1 μmol apoB L −1 , added with the various McPC concentrations to be tested, and then 10‐fold diluted in oxygenated PBS at pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…The polar fraction (methanolic phase) was recovered, whereas the non-polar phase (hexane) followed other methanolic extractions. The fractions obtained were combined and stored at 4°C (Kalantzakis, Blekas, Pegklidou, & Boskou, 2006).Then, total phenolic compounds concentration was estimated by FolinCiocalteu's assay, with absorbance monitored at 760 nm (Monde, Carbonneau, Michel, Lauret, Diabate, Konan, et al, 2011).The result is expressed on a dry weight basis as mg of gallic acid equivalents (GAE) per kg of olive oil (mg GAE kg -1 ).…”
Section: Extraction and Quantification Of Phenolic Compounds From Extmentioning
confidence: 99%